2019
DOI: 10.1038/s41598-018-36552-4
|View full text |Cite
|
Sign up to set email alerts
|

Tupanvirus-infected amoebas are induced to aggregate with uninfected cells promoting viral dissemination

Abstract: The discovery of giant viruses in the last years has fascinated the scientific community due to virus particles size and genome complexity. Among such fantastic discoveries, we have recently described tupanviruses, which particles present a long tail, and has a genome that contains the most complete set of translation-related genes ever reported in the known virosphere. Here we describe a new kind of virus-host interaction involving tupanvirus. We observed that tupanvirus-infected amoebas were induced to aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 29 publications
(34 reference statements)
1
52
0
Order By: Relevance
“…Kyotovirus causes cell-rounding in infected amoeba, as previously reported in other members of the family Marseilleviridae (Boyer et al, 2009;Dos Santos et al, 2016). On the other hand, kashiwazakivirus and hokutovirus lead infected amoeba cells to form "bunches, " as previously reported in tupanviruses (Oliveira et al, 2019). It is not yet understood how "bunches" form after kashiwazaki-and hokutovirus infections, from both amoebal ethological and viral aspects.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Kyotovirus causes cell-rounding in infected amoeba, as previously reported in other members of the family Marseilleviridae (Boyer et al, 2009;Dos Santos et al, 2016). On the other hand, kashiwazakivirus and hokutovirus lead infected amoeba cells to form "bunches, " as previously reported in tupanviruses (Oliveira et al, 2019). It is not yet understood how "bunches" form after kashiwazaki-and hokutovirus infections, from both amoebal ethological and viral aspects.…”
Section: Introductionmentioning
confidence: 58%
“…After infection with a giant virus, Acanthamoeba cells show various morphological and behavioral changes, termed cytopathic effects (CPE), and are then killed. Recent studies have indicated that amoeba cells infected with giant viruses show various CPEs, such as cellrounding, encystment, lysis, and formation of cell aggregates called "bunches" (Reteno et al, 2015;Aoki et al, 2019;Oliveira et al, 2019;Yoshikawa et al, 2019). Among these CPEs, cellrounding or lysis are the common CPEs to check and confirm the infection of amoeba with giant viruses.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the formation of the CPE seems be slower in V. vermiformis than to that previously observed in A. castellanii (Abrahão et al, 2018). We observed that TPV induces in V. vermiformis cell rounding and early cluster formation, the typical “bunches” formed by TPV in amoeba (Oliveira et al, 2019), being visible only around 12 h.p.i., being most evident at 16 and 24 h.p.i. At 36–72 h p.i., we observed bunches disaggregation and lysis (Supplementary Figure S1A).…”
Section: Resultsmentioning
confidence: 79%
“…Tupanviruses were isolated from extreme environments in Brazil and showed unprecedented characteristics, including the ability to replicate in different genera of protozoa (Abrahão et al, 2018). Our data suggest that TPV cycle in V. vermiformis is slower and less productive than TPV replication in A. castellanii (Oliveira et al, 2019; Supplementary Figure S1). The reason why we observe a delay in the evolution of TPV CPE in V. vermiformis requires more investigation as well.…”
Section: Discussionmentioning
confidence: 84%
“…The tupanvirus' infection is characterized by the formation of bunches, aggregate of infected amoebae with uninfected cells. This is the first time this way of increasing viral progeny has been observed in a giant viral infection (Oliveira et al, 2019). Furthermore, it is also the first virus to infect a broad range of hosts, such as Tetrahymena sp., Acanthamoeba castellanii neff, Vermamoeba vermiformis, or Willaertia magna (Abrahão et al, 2018;Silva et al, 2019).…”
Section: Introductionmentioning
confidence: 77%